2015
DOI: 10.1139/gen-2015-0100
|View full text |Cite
|
Sign up to set email alerts
|

The 3-I framework: a framework for developing public policies regarding pharmacogenomics (PGx) testing in Canada

Abstract: The 3-I framework of analyzing the ideas, interests, and institutions around a topic has been used by political scientists to guide public policy development. In Canada, there is a lack of policy governing pharmacogenomics (PGx) testing compared to other developed nations. The goal of this study was to use the 3-I framework, a policy development tool, and apply it to PGx testing to identify and analyze areas where current policy is limited and challenges exist in bringing PGx testing into wide-spread clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…21 It has been suggested that, to affect the level of use of pharmacogenetic results, pharmacists can order pharmacogenetic tests and incorporate results into medication management. 22 We have shown that it is possible for both family physicians and pharmacists to obtain saliva samples from patients, send the samples to the laboratory, complete the biophysical and laboratory data needed for an MDSS and make decisions based on individualized medication options. In a pharmacybased study (n = 54) by Swen and colleagues, 23 9 saliva samples (16.7%) contained too little DNA, whereas we had 1 sample (0.5%) that contained too little DNA.…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been suggested that, to affect the level of use of pharmacogenetic results, pharmacists can order pharmacogenetic tests and incorporate results into medication management. 22 We have shown that it is possible for both family physicians and pharmacists to obtain saliva samples from patients, send the samples to the laboratory, complete the biophysical and laboratory data needed for an MDSS and make decisions based on individualized medication options. In a pharmacybased study (n = 54) by Swen and colleagues, 23 9 saliva samples (16.7%) contained too little DNA, whereas we had 1 sample (0.5%) that contained too little DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The political science model has been extrapolated to the analysis of healthy public policy and impacted the policy process in health issues (10). In healthcare, the framework has been used to aid analysis in studies of evidence-informed policies about health systems, pharmacogenomics policy development, and NCDs policy (11)(12)(13). For this study, this framework could illuminate the processes involved from the formulation to the implementation of NCD policies.…”
Section: Health Sector Policymentioning
confidence: 99%
“…Following other health policy analysts (Lavis et al. 2002 ; Bashir and Ungar 2015 ; Shearer et al. 2016 ; Schram 2018 ), we propose that employing the 3-I framework can provide alcohol researchers with a more sophisticated understanding of how politics shapes the policy process.…”
mentioning
confidence: 97%
“…This is not the first analysis to suggest these factors matter or are interrelated (Heclo 1994;Hall 1997). Following other health policy analysts (Lavis et al 2002;Bashir and Ungar 2015;Shearer et al 2016;Schram 2018), we propose that employing the 3-I framework can provide alcohol researchers with a more sophisticated understanding of how politics shapes the policy process. To our knowledge, this is the first effort to apply this framework to alcohol policy.…”
mentioning
confidence: 99%